2021
DOI: 10.1038/s41598-021-00698-5
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic-mediated p38 MAPK immune signaling prolongs the survival of Caenorhabditis elegans exposed to pathogenic bacteria

Abstract: The host-microbiota cross-talk represents an important factor contributing to innate immune response and host resistance during infection. It has been shown that probiotic lactobacilli exhibit the ability to modulate innate immunity and enhance pathogen elimination. Here we showed that heat-inactivated probiotic strain Lactobacillus curvatus BGMK2-41 stimulates immune response and resistance of the Caenorhabditis elegans against Staphylococcus aureus and Pseudomonas aeruginosa. By employing qRT-PCR and western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
4
13
0
1
Order By: Relevance
“…Probiotics are a promising approach to improve salmon weight gain and disease resistance, offering potential solutions for the two major challenges in aquaculture. Lactobacillus , first bacteriologically described in 1901 14 , is a popular probiotic candidate genus of lactic acid bacteria with a long history of safe use 15 , 16 , and many studies have shown their efficacy in modulating terrestrial host immune systems 17 20 . They dominate the intestine of healthy fish 21 , 22 and favorably modulate fish gut microbiome 22 , suggesting that they may be adapted for survival in the fish gut environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics are a promising approach to improve salmon weight gain and disease resistance, offering potential solutions for the two major challenges in aquaculture. Lactobacillus , first bacteriologically described in 1901 14 , is a popular probiotic candidate genus of lactic acid bacteria with a long history of safe use 15 , 16 , and many studies have shown their efficacy in modulating terrestrial host immune systems 17 20 . They dominate the intestine of healthy fish 21 , 22 and favorably modulate fish gut microbiome 22 , suggesting that they may be adapted for survival in the fish gut environment.…”
Section: Introductionmentioning
confidence: 99%
“…They dominate the intestine of healthy fish 21 , 22 and favorably modulate fish gut microbiome 22 , suggesting that they may be adapted for survival in the fish gut environment. Lactobacilli have been repeatedly demonstrated to improve fish disease resistance via immunostimulation 17 20 . This effect likely stems from a combination of mechanisms such as humoral immune modulation 21 , 22 , bacteriocin production 23 , and lymphocyte modulation 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Western Balkan countries (WBCs) have a long and rich experience in the production of artisanal dairy products, known for their diversity of LAB species and strains, with highly diverse health-promoting properties related to certain pathological conditions, e.g., diabetes, inflammatory pain, gut–brain axis-related diseases, aging, etc. [ 24 , 25 , 26 , 27 , 28 ]. However, up to now, the molecular mechanisms implicated in the effects of probiotics in respiratory epithelial cells have not been investigated though these species represent common members of healthy human lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are a promising approach to improve salmon weight gain and disease resistance, offering potential solutions for the two major challenges in aquaculture. Lactobacillus, rst bacteriologically described in 1901 (14), is a popular probiotic candidate genus of lactic acid bacteria with a long history of safe use (15,16), and many studies have shown their e cacy in modulating terrestrial host immune systems (17)(18)(19)(20). They dominate the intestine of healthy sh (21,22) and favorably modulate sh gut microbiome (22), suggesting that they may be adapted for survival in the sh gut environment.…”
Section: Introductionmentioning
confidence: 99%
“…They dominate the intestine of healthy sh (21,22) and favorably modulate sh gut microbiome (22), suggesting that they may be adapted for survival in the sh gut environment. Lactobacilli have been repeatedly demonstrated to improve sh disease resistance via immunostimulation (17)(18)(19)(20). This effect likely stems from a combination of mechanisms such as humoral immune modulation (21,22), bacteriocin production (23), and lymphocyte modulation (24,25).…”
Section: Introductionmentioning
confidence: 99%